Transfer of improved farm production technologies for enhancement of rural livelihood security amongst the farm households of Kangra district of Himachal Pradesh - Chaudhary, D R; Rana, S S; Bhushan, Lav; Kumar, Suresh; Sharma, Pawan; Kumar, Parvesh; Sharma, K D; Thakur, Y P; Kumar, Arvind; Singh, Rajbir; Sarial, A K (Indian Farming, 2022)
Mushroom, Nutri-gardens, Vegetable cultivation